Heat shock proteins in atrial fibrillation: from bench to bedside - Zhang, Shujie; Wang, Yujie; Nie, Lujing; Feng, Wenjiu; Zhang, Mengyuan; Chen, Yanbo (Frontiers in Physiology, 2025)
Atrial fibrillation (AF) is the most common age-related arrhythmia in clinic, affecting millions of people around the world, and is closely related to heart failure, ischemic stroke and other diseases. In addition, AF is progressive in nature and represents a significant global health burden. However, the current treatment plans are mainly symptomatic, the efficacy in preventing atrial fibrillation is limited. Hence, there is a pressing need for etiology-specific AF treatments. It is widely acknowledged that the atrial electrical and structural remodeling constitutes the pathological basis of atrial fibrillation. Evidence indicates that heat shock proteins (HSPs) could have a protective effect against AF. HSPs are a diverse family of molecular chaperones that safeguard cells against various stressors. They play a crucial role in mitigating oxidative stress, inflammation, and apoptosis, thereby helping to prevent structural and electrical remodeling in cardiomyocytes. Moreover, HSPs safeguard proteostasis via prevention of toxic protein aggregation by binding to (partially) unfolded proteins. As pivotal inhibitors of AF onset and progression, HSPs represent both a promising therapeutic target and potential biomarkers for staging AF and predicting post-treatment recurrence, as evidenced by recent studies. In this review, we explore the mechanisms of HSP in AF to pave the way for the development of targeted therapies for this prevalent arrhythmia disease.